Reading architectural working drawings residential and light construction - Muller, Edward John 1916-; Grau, Philip A. 1951- (Prentice Hall, 2000)
This workbook is ideal for those who want to refresh or test their knowledge base for reading today's architectural working drawings--including the full range of currently-used traditional and more modern procedures and techniques, terminology, etc. Features real working drawings (reduced to a manageable size), and worksheets covering the essentials of drawing, mathematics, geometry, terminology, materials, and systems--all focused around the details of residential and light construction. Includes a section on Computer-Aided Drafting--contemporary computer systems, hardware and software, and the Internet in design and construction. A section specifications covers the changes made in the 1995 edition of CSI Masterformat and Manual of Practice. For architects, designers, and construction personnel who want a refresher or up-date.